ARTIFICIAL INTELLIGENCE IN TRANSPORTATION: A PARADIGM SHIFT IN MOBILITY AND URBAN PLANNING - Venkata Rajesh Krishna Adapa (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Artificial Intelligence (AI) is rapidly transforming the transportation sector, ushering in a new era of mobility and urban planning. This article examines the multifaceted impact of AI on transportation systems, focusing on three key areas: autonomous vehicles, traffic management, and logistics optimization. Through a comprehensive review of current literature and case studies, we analyze how AI-driven technologies are enhancing transportation efficiency, safety, and sustainability. The article explores the potential of self-driving cars to reduce accidents and congestion, the role of AI in optimizing traffic flow and urban infrastructure, and its application in streamlining supply chains and last-mile delivery. Furthermore, we discuss the implications of these advancements for urban planning and design, considering both the opportunities and challenges they present. The article also addresses critical issues such as data privacy, regulatory frameworks, and the socioeconomic impacts of AI in transportation. The findings suggest that while AI holds immense promise for revolutionizing mobility, its successful integration requires careful consideration of technological, ethical, and policy factors. This article contributes to the growing body of knowledge on smart transportation systems and provides insights for policymakers, urban planners, and technology developers in shaping the future of sustainable and intelligent mobility.